Virtual Preaching Activism In Indonesia: Social Media, Politic of Piety, New Ulama, and Democracy - Muhammad Said (IAIN Pekalongan, 2020)
This paper problematizes the dynamic of contemporary virtual preacher’s role in Indonesia and its religious border, cultural, social, and political impact. Indeed, the new media and social networks gave the preacher a pivotal social figure, a cultural broker, and an authoritative interpreter of religion. The current phenomenon of the rise of social media in da'wa participation has a significant impact on Indonesia's socio-political life. The production of religious knowledge through virtual preaching activism is in line with discourse battles, contestation of authority, and politics. This phenomenon also has an impact on the internal relations among Muslims and between religious communities as well. Therefore, by using ethnographical social-media analysis, this paper examines some research questions below: (1) what the social media can tell us regarding the shifting from traditional religious knowledge to electronic spiritual understanding? (2) how the new ulama develop authority in the online society era? (3) how the politic of piety deal with democracy?